Genetic Analysis Workshop 18: methods and strategies for analyzing human sequence and phenotype data in members of extended pedigrees - Bickeböller, Heike; Bailey, Julia N.; Beyene, Joseph; Cantor, Rita M.; Cordell, Heather J.; Culverhouse, Robert C.; Engelman, Corinne D.; Fardo, David W.; Ghosh, Saurabh; König, Inke R.; Lorenzo Bermejo, Justo; Melton, Phillip E.; et al. (BMC proceedings, 2014)
Genetic Analysis Workshop 18 provided a platform for developing and evaluating statistical methods to analyze whole-genome sequence data from a pedigree-based sample. In this article we present an overview of the data sets and the contributions that analyzed these data. The family data, donated by the Type 2 Diabetes Genetic Exploration by Next-Generation Sequencing in Ethnic Samples Consortium, included sequence-level genotypes based on sequencing and imputation, genome-wide association genotypes from prior genotyping arrays, and phenotypes from longitudinal assessments. The contributions from individual research groups were extensively discussed before, during, and after the workshop in theme-based discussion groups before being submitted for publication.